Melanocortin regulation of histaminergic neurons via perifornical lateral hypothalamic melanocortin 4 receptors - Natalie J. Michael; Alexandre Caron; Charlotte E. Lee; Carlos M. Castorena; Syann Lee; Jeffrey M. Zigman; Kevin W. Williams; Joel K. Elmquist (Elsevier, 2020)
Objective: Histaminergic neurons of the tuberomammillary nucleus (TMN) are wake-promoting and contribute to the regulation of energy homeostasis. Evidence indicates that melanocortin 4 receptors (MC4R) are expressed within the TMN. However, whether the melanocortin system influences the activity and function of TMN neurons expressing histidine decarboxylase (HDC), the enzyme required for histamine synthesis, remains undefined. Methods: We utilized Hdc-Cre mice in combination with whole-cell patch-clamp electrophysiology and in vivo chemogenetic techniques to determine whether HDC neurons receive metabolically relevant information via the melanocortin system. Results: We found that subsets of HDC-expressing neurons were excited by melanotan II (MTII), a non-selective melanocortin receptor agonist. Use of melanocortin receptor selective agonists (THIQ, [D-Trp8]-γ-MSH) and inhibitors of synaptic transmission (TTX, CNQX, AP5) indicated that the effect was mediated specifically by MC4Rs and involved a glutamatergic dependent presynaptic mechanism. MTII enhanced evoked excitatory post-synaptic currents (EPSCs) originating from electrical stimulation of the perifornical lateral hypothalamic area (PeFLH), supportive of melanocortin effects on the glutamatergic PeFLH projection to the TMN. Finally, in vivo chemogenetic inhibition of HDC neurons strikingly enhanced the anorexigenic effects of intracerebroventricular administration of MTII, suggesting that MC4R activation of histaminergic neurons may restrain the anorexigenic effects of melanocortin system activation. Conclusions: These experiments identify a functional interaction between the melanocortin and histaminergic systems and suggest that HDC neurons act naturally to restrain the anorexigenic effect of melanocortin system activation. These findings may have implications for the control of arousal and metabolic homeostasis, especially in the context of obesity, in which both processes are subjected to alterations. Keywords: Histaminergic neurons, Melanocortin, Lateral hypothalamus, Food intake, MC4R, Electrophysiology